Coronary Plaque Characteristics Assessed by 256-Slice Coronary CT Angiography and Association with High-Sensitivity C-Reactive Protein in Symptomatic Patients with Type 2 Diabetes - Jinling Zhang; Zhehao Lv; Deli Zhao; Lili Liu; Yong Wan; Tingting Fan; Huimin Li; Ying Guan; Bailu Liu; Qi Yang (Journal of Diabetes Research)
Little is known regarding plaque distribution, composition, and the association with inflammation in type 2 diabetes mellitus (DM2). This study aimed to assess the relationship between coronary plaque subtypes and high-sensitivity C-reactive protein levels. Coronary CTA were performed in 98 symptomatic DM2 patients and 107 non-DM2 patients using a 256-slice CT. The extent and types of plaque as well as luminal narrowing were evaluated. Patients with DM2 were more likely to have significant stenosis (>50%) with calcified plaques in at least one coronary segment (p<0.01); the prevalence rates of diffuse calcified plaques in the DM2 and non-DM2 groups were 31.6% and 4.7%, respectively (p<0.01). Plasma hs-CRP levels in DM2 with calcified plaques were higher compared with values obtained for the non-DM2 group (p<0.01). In conclusion, combination of coronary CTA and hs-CRP might improve risk stratification in symptomatic DM2 patients.